INOVASI PENDIDIKAN : UPAYA PENYELESAIAN PROBLEMATIKA PENDIDIKAN DI INDONESIA - Kadi, Titi; Awwaliyah, Robiatul (JURNAL ISLAM NUSANTARA, 2017)
This paper presents the importance of educational innovation, as part of the effort to solve the peroblematic education in Indonesia. Education and society are two sides that have reciprocal relations, that is, what is going on in the world of education, is a true picture in the reality of complex community life. However, the reciprocal relationship formula is not always directly proportional. Communities developing in high escalation and progressiveness, while the world of education, are still busy with a variety of problems that are not easily broken down. Based on the explanation, innovation in the world of education is very urgent to be done by every human being who has concern for the development of education, as a form of improvement towards better education of Indonesia.